2007
DOI: 10.1007/s10802-007-9161-0
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use in Adolescent Twins and Affiliation with Substance Using Peers

Abstract: Affiliation with substance using peers is one of the strongest predictors of adolescent alcohol use. This association is typically interpreted causally: peers who drink incite their friends to drink. This association may be complicated by uncontrolled genetic and environmental confounds because teens with familial predispositions for adolescent substance use may be more likely to select into social networks where drinking is common. We test this alternative hypothesis using a sample of 1,820 twin and sibling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 42 publications
4
36
1
1
Order By: Relevance
“…Similarly, Harden and colleagues (2008) reported support for both rGE and social influence; shared environmental factors were not found to be significant in that sample, which focused on adolescent substance use and peer groups. Finally, Hill and colleagues (2008) found evidence of genetic correlation, but not of social influence. All these reports used different modeling approaches than those employed in the current study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, Harden and colleagues (2008) reported support for both rGE and social influence; shared environmental factors were not found to be significant in that sample, which focused on adolescent substance use and peer groups. Finally, Hill and colleagues (2008) found evidence of genetic correlation, but not of social influence. All these reports used different modeling approaches than those employed in the current study.…”
Section: Discussionmentioning
confidence: 93%
“…We are also limited to self-reports, which might be subject to bias. Similarly, some evidence suggests that self-reports of peer behavior overestimate the similarity between one’s own behavior and that of their peers (Hill et al, 2008). Data were only available for men, and there is potential for gender differences in the role of peer influences on drinking (Dick et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Irons et al (18) study, we found no rGE between ALDH2 *2 status and our measure of the peer environment. Genetic susceptibility for substance use and peer selection are correlated, but likely attributed to other genes than those for alcohol metabolism (40,41). For example, Chassin et al (42) and Mrug and Windle (43), respectively, studied dopamine receptor ( DRD4 ) and μ-opioid receptor M1 ( OPRM1 ) genes in association with alcohol use behaviors and found evidence for both genetically influenced peer selection and gene–environment interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Jugendliche mit ähnli-chen genetisch angelegten Temperamentsmerkmalen etwa hinsichtlich des Risikoverhaltens könnten sich sowohl zueinander als auch zu Alkohol oder Drogen hingezogen fühlen (Dick et al 2007;Hill et al 2008). So können der Alkohol-und Drogenmissbrauch von Freunden ebenso aufgrund ihrer genetischen Ähnlichkeiten korreliert sein wie aufgrund ihrer Sozialisationserfahrungen, auch wenn der Gruppendruck der Freunde beim jugendlichen Trinken nicht ausschließlich genetisch bedingt ist (Cruz et al 2012).…”
Section: Alkohol Und Drogenmissbrauchunclassified